Efek Celebrity Endorser Terhadap Minat Beli Iklan Luwak White Koffie - Wati, Enggi Wiyata Mandala (The Journal of Communication Management and Organization, 2022)
Celebrity endorser is utilizing an artist, entertainer, athlete, and public figure who is known to the public because of his ability in a field that can support the product he is promoting. Buying interest is something related to consumers' plans to buy certain products and how many units of product are needed in a certain period. This study aims to determine the effect of celebrity endorser on Luwak White Koffie advertisements on buying interest. The research population was students of the Faculty of Communication Science 2015-2016 active students totaling 269 people, the research sample was 100 people using probability sampling technique. The research method used is a survey method and questionnaire data collection techniques and simple regression data analysis. The results of this study indicate that there is an influence between celebrity endorsers on buying interest. The magnitude of the influence of celebrity endorsers on buying interest is 36.7% and the remaining 63.3% are other factors, the probability value of 0.000 <0.05 has a significant influence.